THE INFLUENCE OF GENDER STEREOTYPES IN FORMING IMMUNITY AGAINST INFORMATION ATTACKS IN ADOLESCENT CHILDREN. (Universal International Scientific Journal, 2026)
This article analyzes the influence of gender stereotypes on the process of forming immunity to information attacks in adolescents. In the context of the widespread development of information technologies and social networks, adolescents are increasingly exposed to various ideological, psychological and cultural information attacks. At the same time, it is important to develop their critical thinking, form the ability to make independent decisions, and strengthen their skills in analyzing information.
Keywords: Family; society; seteritype